The right to education in Latin America for the COVID-19 pandemic: main obstacles and challenges - Sánchez Lora, Juan Carlos (2022)
This article examines the impact that the covid-19 pandemic had on learning and the right to education in Latin America. This study assesses whether remote education policies that Governments in the region issued considered the international standards provided by the International System for the Protection of Human Rights (ISPHR). The aim of the assessment was to verify whether policies effectively provided continuity to learning and supported the right to education. An analytical and descriptive methodology that used international human rights treaties, reports issued by ISPHR allied organisations and public policies implemented by governments in educational matters, helped to identify the problems that made the application of this education policies in Latin American countries unsuccessful. It is concluded that, given its devastating effects, the advent of covid-19 further aggravated the shortcomings of national education systems, most of which failed to ensure inclusive and quality education in line with international standards.